(Nie)Etyczna Unia Europejska na Bałkanach - Pawlak, Mateusz (Annales. Etyka w Życiu Gospodarczym, 2013)
Although all the Western Balkan countries have been offered the prospect of European Union (EU) membership, the accession process still constitutes a complicated and multi-aspect challenge. EU support and engagement in the region have resulted in a few successes, nonetheless, describing them as major breakthroughs is far from the reality. Since the establishment of the Dayton Agreement in 1995, ending the conflict in Bosnia and Herzegovina, most of the Balkan states have not managed to accomplish their political, ideological and civic transformations yet. However, the difficult situation and frequent negotiation stalemates are not only the outcomes of the unsatisfactory progress made by the Peninsular countries. Ambiguous and unethical (in some cases) behaviour can also be noticed from the EU decision-makers’ side. The following article aims to present concrete examples of EU external policy actions in Bosnia and Herzegovina which can be described as controversial. However, the author attempts to prove the thesis that unethical external policy is not always a zero-sum game, and in particular circumstances it can be paradoxically perceived as the best solution. Taking into consideration the comprehensiveness of the problem and editorial limitations, the analysis focuses on activities of the High Representative for Bosnia and Herzegovina, who used to be (during four out of seven tenures) the EU Special Representative for Bosnia and Herzegovina.